Answer:
Given system of equations,
y = - x ------(1)
y = x - 1 ------(2),
From equation (1) and (2),
-x = x - 1
-x - x = -1
-2x = -1
![\implies x = (1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9lutctnztgwdm6p77xhc02lbe1ufh8s6il.png)
Again from equation (1),
![y = -(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/s8lr3o4t3i2vi6e92as5s513t8181x6ob5.png)
Thus, the intersection point of the lines (1) and (2), is
![((1)/(2), -(1)/(2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wqo1a4hjlmj0ff2p0a4cjd5pvkfyvb2zg0.png)
Hence, the below graph represents the solution to the system of equations.